1999
DOI: 10.1007/s005350050372
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori infection correlates with severity of reflux esophagitis: with manometry findings

Abstract: The role of Helicobacter pylori infection in the development and exacerbation of reflux esophagitis was investigated. The prevalence of Helicobacter pylori infection, the severity of atrophic gastritis, and esophageal motility (determined by esophageal manometry by an infusion catheter method) were assessed in patients with mild (n = 46) and severe (n = 27) reflux esophagitis and subjects without reflux (n = 28). Compared with the prevalence of Helicobacter pylori infection in the non-reflux group, the prevale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 26 publications
5
63
0
4
Order By: Relevance
“…We verified the development of erosive esophagitis in 19% of them after H. pylori eradication, similarly to RAGHUNATH et al (34) systematic review publication.…”
Section: Discussionsupporting
confidence: 85%
“…We verified the development of erosive esophagitis in 19% of them after H. pylori eradication, similarly to RAGHUNATH et al (34) systematic review publication.…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, although we examined chronological changes in the degree of gastric mucosal atrophy on endoscopy, the status of H. pylori infection was not assessed. H. pylori infection has repeatedly been reported to influence gastric acid secretion and the prevalence of reflux esophagitis (31)(32)(33). Therefore, future studies are required to clarify the effects of timecourse changes in the rate of H. pylori infection on the prevalence of GERD.…”
Section: Discussionmentioning
confidence: 99%
“…The incidences of RE in patients with disease durations of less than 6 years, 6 to 11 years, 11 to 16 years, and more than 16 years were 11.8% (2/17), 10 respectively. The incidence of RE tended to rise with increased duration of the disease.…”
Section: The Incidence Of Re and Gerd In Patients According To Diseasmentioning
confidence: 94%
“…Some investigators have reported that the incidence of H pylori infection in diabetic patients is higher than controls [9][10][11][12][13] . Some investigators have reported that in DM patients, due to impaired immune function and impaired gastrointestinal motility, they were prone to H pylori infection [36][37][38] .…”
Section: Ariizumi K Et Al H Pylori and Re In Diabetic Patientsmentioning
confidence: 99%
See 1 more Smart Citation